2019
DOI: 10.3390/cancers11081087
|View full text |Cite
|
Sign up to set email alerts
|

Novel Apoptosis-Inducing Agents for the Treatment of Cancer, a New Arsenal in the Toolbox

Abstract: : Evasion from apoptosis is an important hallmark of cancer cells. Alterations of apoptosis pathways are especially critical as they confer resistance to conventional anti-cancer therapeutics, e.g., chemotherapy, radiotherapy, and targeted therapeutics. Thus, successful induction of apoptosis using novel therapeutics may be a key strategy for preventing recurrence and metastasis. Inhibitors of anti-apoptotic molecules and enhancers of pro-apoptotic molecules are being actively developed for hematologic maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 307 publications
(377 reference statements)
2
39
0
Order By: Relevance
“…On the other, very often, mutations in cancer cells make them unable to deliver one or the other pathway [3]. Indeed, apoptosis inducers offer promises for achieving, in both normal and malignant cells, a decreased toxicity coupled with an improved therapeutic outcome [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…On the other, very often, mutations in cancer cells make them unable to deliver one or the other pathway [3]. Indeed, apoptosis inducers offer promises for achieving, in both normal and malignant cells, a decreased toxicity coupled with an improved therapeutic outcome [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Because the gene encoding protein p53 is often mutated in cancers, TRAIL's ability to activate apoptosis independently of the p53, together with its tumor-selectivity, made TRAIL an attractive therapeutic target ( Elmore, 2007 ; Lim et al, 2019 ). Yet, owing to TRAIL's ability to bind to four TRAIL receptors with a similarly high affinity, the understanding of TRAIL signaling regulation represents a grand challenge ( Micheau et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Obatoclax, a synthetic derivative of bacterial prodiginines [21], is a clinically developed small-molecule pan-BCL-2 inhibitor that functions by blocking BH3-mediated binding of BH3-only proteins or BAX/BAK to antiapoptotic BCL-2, BCL-xL, and MCL-1, causing BAX/BAK activation to trigger apoptosis [22]. Phase I/II clinical trials have revealed the anticancer potential of Obatoclax as a single agent or in combination with other chemo-and radiation therapies [23][24][25]. Notably, given overexpression of antiapoptotic BCL-2 family members is closely linked to therapeutic resistance in cancer cells, Obatoclax has been demonstrated to facilitate drug sensitization of chemoresistant cells in both hematological [23] and solid tumors [26].…”
Section: Introductionmentioning
confidence: 99%